Neurophysiological and Neurochemical Effects of the Putative Cognitive Enhancer (S)-CE-123 on Mesocorticolimbic Dopamine System - Claudia Sagheddu; Nicholas Pintori; Predrag Kalaba; Vladimir Dragačević; Gessica Piras; Jana Lubec; Nicola Simola; Maria Antonietta De Luca; Gert Lubec; Marco Pistis (Biomolecules, 2020)
Treatments for cognitive impairments associated with neuropsychiatric disorders, such as attention deficit hyperactivity disorder or narcolepsy, aim at modulating extracellular dopamine levels in the brain. CE-123 (5-((benzhydrylsulfinyl)methyl) thiazole) is a novel modafinil analog with improved specificity and efficacy for dopamine transporter inhibition that improves cognitive and motivational processes in experimental animals. We studied the neuropharmacological and behavioral effects of the S-enantiomer of CE-123 ((S)-CE-123) and R-modafinil in cognitive- and reward-related brain areas of adult male rats. In vivo single unit recordings in anesthetized animals showed that (S)-CE-123, but not R-modafinil, dose-dependently (1.25 to 10 mg/kg i.v.) reduced firing of pyramidal neurons in the infralimbic/prelimbic (IL/PrL) cortex. Neither compound the affected firing activity of ventral tegmental area dopamine cells. In freely moving animals, (S)-CE-123 (10 mg/kg i.p.) increased extracellular dopamine levels in the IL/PrL, with different patterns when compared to R-modafinil (10 mg/kg i.p.); in the nucleus accumbens shell, a low and transitory increase of dopamine was observed only after (S)-CE-123. Neither (S)-CE-123 nor R-modafinil initiated the emission of 50-kHz ultrasonic vocalizations, a behavioral marker of positive affect and drug-mediated reward. Our data support previous reports of the procognitive effects of (S)-CE-123, and show a minor impact on reward-related dopaminergic areas.